Photovoltaic Studies of Cd1-xCoxS Based Electrochemical Cells - Deshmukh, L. P.; Mane, S. T.; Lendave, S. A.; Pingale, P. C.; Suryawanshi, R. V.; Pirgonde, B. R. (Journal of Nepal Chemical Society, 2013)
The Cd1-xCoxS (0 ≤ x ≤ 0.5) thin films were deposited on chemomechanically and ultrasonically cleaned stainless steel substrates by a liquid phase chemical bath deposition technique. The preparative parameters, (viz. growth temperature (56°C), deposition time (80 minutes), reaction pH (11±0.2) and the rate of mechanical churning (70±2)) and deposition conditions were used as optimized previously. The electrode/electrolyte interfaces were then set up between the n-type Cd1-xCoxS (0 ≤ x < 0.5) photosensing electrodes and a sulphide/polysulphide (0.25 M ) redox electrolyte in H-shaped corning glass cells. A graphite rod treated in a cobalt sulphate solution for 24 hours was employed as a counter electrode. The as- fabricated cells were then characterized through the voltage-current and voltage-capacitance characteristics in dark, photovoltaic power output characteristics under constant illumination, and different responses of the cells to incident light. The PV performance parameters such open-circuit photopotential (Vph), short circuit photocurrent (Iph), series and shunt resistances (Rs & Rsh), efficiency (η), form factor (ff), dark ideality factor (nd), ideality factor under illumination(nL), built-in potential (ΦB), dark current (ID), the flat band potential(Vfb), junction capacitance under flat band condition (cj), cut off wavelength(λc) and photogenerated carrier life time(τ) were evaluated for various cells with a special emphasis given to the electrode composition (x). In general, photovoltaic output performance of the Cd1-XCoXS based electrochemical cell is improved after Co implantation (x=0.1) in CdS. DOI: http://dx.doi.org/10.3126/jncs.v30i0.9387 Journal of Nepal Chemical Society Vol. 30, 2012 Page: 151-158 Uploaded date: 12/20/2013